Metody odběru vzorku na kultivační vyšetření v chirurgické praxi, otiskové metody - Chovanec, Z; Veverková, L; Votava, M; Svoboda, J; Peštál, A; Doležel, J; Jedlička, V; Veselý, M; Wechsler, J; Čapov, I (Rozhledy v chirurgii, 2012)
The wound is a damage of tissue. The process of healing is influenced by many systemic and local factors. The most crucial and the most discussed local factor of wound healing is infection. Surgical site infection in the wound is caused by micro-organisms. This information is known for many years, however the conditions leading to an infection occurrence have not been sufficiently described yet. Correct sampling technique, correct storage, transportation, evaluation, and valid interpretation of these data are very important in clinical practice. There are many methods for microbiological sampling, but the best one has not been yet identified and validated. We aim to discuss the problem with the focus on the imprint technique.
Keywords: odběr biologického vzorku; Humans; Specimen Handling; infekce chirurgické rány; Surgical Wound Infection; lidé